Recent advances in the use of animal-sourced gelatine as natural polymers for food, cosmetics and pharmaceutical applications - Mohd Shakrie Palan Abdullah,; Mohamed Ibrahim Noordin,; Syed Ibrahim Mohd Ismail,; Nur Murnisa Mustapha,; Malina Jasamai,; Mohd Fairuz Danik,; Wan Azman Wan Ismail,; Ahmad Fuad Shamsuddin, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Gelatine is used as an excipient for various pharmaceutical dosage forms, such as capsule shells (both hard and soft), tablets, suspensions, emulsions and injections (e.g. plasma expanders). It is also broadly used in various industries such as food and cosmetics. Gelatine is a biopolymer obtained from discarded or unused materials of bovine, porcine, ovine, poultry and marine industrial farms. The discarded materials can be the skin, tendons, cartilages, bones and connective tissues. Gelatine sourced from animals is relatively easy and inexpensive to produce. The potential needs of gelatine cannot be overemphasised. Rising demands, health concerns and religious issues have heightened the need for alternative sources of gelatine. This review presents the various industrial uses of gelatine and the latest developments in producing gelatine from various sources.